Adverse events involving mandibular hardware: an analysis of the Food and Drug Administration Facility Device Experience data. (20th July 2018) - Elias, M. L.; Weisberger, J. S.; Barinsky, G. L.; Paskhover, B.
Abstract: Purpose: To investigate frequencies and characteristics concerning mandibular device complications as reported to the Food and Drug Administration. Study Design: Retrospective database review. Methods: The Manufacturer and User Facility Device Experience (MAUDE) database was queried for reports from 2007 to 2017 using the keywords 'mandible' and 'mandibular'. A total of 3592 reports were gathered. After curating out duplicate reports, reports not applicable to mandibular hardware, and literature articles, 1899 event device reports were subsequently studied for mandibular hardware. A side cohort of 192 TMJ device reports was analysed separately. Reports were reviewed based on both the device cited in the report and the concerns cited in the event text (i.e. an explanation of a plate fracture/failure or of an infection). Additional frequencies involving the company manufacturers and reported patient injury were also analysed. Results: The majority of the 1899 mandibular device reports cited screw failures (20.4%), infection (15.8%), plate fracture (12.9%), or distractor malfunction (7.9%). Of all the records, 60.3% self‐categorised themselves as 'injury' events, whereas 36.4% self‐classified as 'malfunction' reports. The plate fractures consisted of 79.8% occurring post‐operatively and 14.0% intra‐operatively. A majority of the implicated screw failures were regular, non‐intermaxillary fixation/mandibulomaxillary fixation screws (75.3%). Depuy Synthes (59.6%) and Stryker (16.6%) were most often implicated in these 1899 mandibular reports. Of the separate 192 TMJ reports, the events indicated mainly jaw pain 32.0%, incorrect fit of the device (11.2%), infection (10.7%), loose screws (9.6%), and dislocation in the patient post‐operatively (7.6%), with Biomet involved in the majority of reports (90.8%). Conclusions: The MAUDE reports on mandibular devices correspond with the major adverse events cited in previous literature. The reports delineate areas of improvement for both manufacturers (i.e. post‐operative hardware failure and intra‐operative equipment failures) verses probable user error (i.e. intra‐operative plate and patient injuries).